Multifunctional Antenna with High Isolation for Interweave and Underlay Operation in Cognitive Radio - Rathore P.S.; Mali R.; Jatav R.; Meshram M.K. (My University, 2025)
This paper presents a multifunctional antenna with high isolation for interweave and underlay cognitive radio (CR) applications.The proposed antenna consists of an ultra-wideband (UWB) antenna (ANT1) for sensing and communication in UWB spectrumrange and a frequency reconfigurable antenna (ANT2) for communication over frequency ranges from 3 to 3.7 GHz and 3.8 to 5.6 GHz.The proposed antenna is designed on an FR-4 substrate 50 × 65 × 1.6 mm3 with a shared ground plane. A square slot and a rectangularstub is introduced in the ground plane to achieve −10 dB wide impedance bandwidth and good isolation over the frequency range of 1.8to 12 GHz. An underlay CR operation is attained with a UWB ANT1 with reconfigurable band notch of 2.76 to 3.7 GHz by introducinga U-shaped slot. The interweave operation is obtained by incorporating ANT1 and ANT2 in the same substrate. ANT1 without notchband is used for sensing spectrum, and ANT2 with reconfigurable frequency is used for communication. The proposed antenna attainsinterweave and underlay operations with inter-port isolation greater than 17 dB all over the proposed UWB and communication band. © (2024), (Electromagnetics Academy). All rights reserved.